Heterogeneity in the local employment multipliers in the United States. (2nd July 2019) - Osei, Michael J.; Sengupta, Shruti
Abstract: Recent studies have found evidence of a local employment multiplier's effect. For the most part, these studies provide an average estimate for all labor markets. In this paper, we examine how the average local employment multiplier, the effect of an exogenous increase in employment in the tradable sector on total employment, depends on the characteristics of the local labor market. Specifically, we estimate the average multipliers for coastal, noncoastal, large, and small metropolitan statistical areas (MSAs) across different time periods using the data of 333 US MSAs. Overall, we find a reduced form of local employment multiplier ranging from 1.38 to 2.24, which is within the range of typically estimated local employment multipliers. In addition, the characteristics of the local labor market matter. The local multipliers appear larger in noncoastal and large MSAs. For small and coastal metros, the multiplier is closer to 1.5 than to 2.0 while in the case of large and noncoastal metros, it is closer to 2.0 than to 1.5. The local multipliers are also sensitive to the time period considered.